(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of women in society through the works of Ismoilbek Gaspirali, a Crimean Tatar enlightener and founder of the Jadid movement, who lived in the late 19th and early 20th centuries. It also analyzes some articles about the situation of women in Turkestan published in the women’s newspaper "Olam Nisvan".